Mission in the New Testament, with Emphasis on Mark’s Gospel - Sewakpo, Honore (International bulletin of mission research, 2020)
Jesus Christ directly commanded the early church to carry the Gospel to other places. Literature on mission has focused largely on its role in Matthew, Luke-Acts, and John, with little attention paid to Mark and its contribution to Jesus’s mandate for mission. I examine Mark’s gospel to discover insights regarding how Jesus carried out his mission, discussing (1) Mark’s soteriological, cultural, and ecclesiological interpretations of mission; (2) the text’s approaches to mission as kērygma, diakonia, and koinōnia; and (3) its view of missions as both centrifugal and centripetal.